2019
DOI: 10.1002/jnr.24397
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide mononucleotide alters mitochondrial dynamics by SIRT3‐dependent mechanism in male mice

Abstract: Nicotinamide adenine dinucleotide (NAD+) is a central signaling molecule and enzyme cofactor that is involved in a variety of fundamental biological processes. NAD+ levels decline with age, neurodegenerative conditions, acute brain injury, and in obesity or diabetes. Loss of NAD+ results in impaired mitochondrial and cellular functions. Administration of NAD+ precursor, nicotinamide mononucleotide (NMN), has shown to improve mitochondrial bioenergetics, reverse age‐associated physiological decline, and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 79 publications
5
33
0
Order By: Relevance
“…These findings reveal a mitochondria-mediated mechanism that may contribute to the previously reported beneficial effects of KE treatment on cognition and A␤ and pTau pathologies in 3xTgAD mice (Kashiwaya et al, 2013), as well as the ability of the combination of pyruvate and ␤-hydroxybutyrate to reduce hyperexcitability in AppPs1 mice (Zilberter et al, 2013). Bolstering mitochondrial NAD ϩ levels with the NAD ϩ precursors nicotinamide and nicotinamide riboside is another approach for enhancing SIRT3 activity and protecting neurons against A␤ and oxidative stress (Liu et al, 2013;Hou et al, 2018;Klimova et al, 2019). Interestingly, exercise and intermittent fasting protect against neuronal dysfunction and cognitive impairment in multiple mouse models of AD and other disorders that involve neuronal excitability (Wang et al, 2005;Halagappa et al, 2007;Nichol et al, 2007;Nigam et al, 2017, and also induce expression of SIRT3 in hippocampal and cortical neurons (Cheng et al, 2016;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…These findings reveal a mitochondria-mediated mechanism that may contribute to the previously reported beneficial effects of KE treatment on cognition and A␤ and pTau pathologies in 3xTgAD mice (Kashiwaya et al, 2013), as well as the ability of the combination of pyruvate and ␤-hydroxybutyrate to reduce hyperexcitability in AppPs1 mice (Zilberter et al, 2013). Bolstering mitochondrial NAD ϩ levels with the NAD ϩ precursors nicotinamide and nicotinamide riboside is another approach for enhancing SIRT3 activity and protecting neurons against A␤ and oxidative stress (Liu et al, 2013;Hou et al, 2018;Klimova et al, 2019). Interestingly, exercise and intermittent fasting protect against neuronal dysfunction and cognitive impairment in multiple mouse models of AD and other disorders that involve neuronal excitability (Wang et al, 2005;Halagappa et al, 2007;Nichol et al, 2007;Nigam et al, 2017, and also induce expression of SIRT3 in hippocampal and cortical neurons (Cheng et al, 2016;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies (Torrens-Mas et al, 2019) have shown that SIRT3 regulates mitochondrial biosynthesis by activating PGC-1a. NAD+ is necessary as a cofactor for SIRT3 deacetylation (Klimova et al, 2019); as a result, SIRT3 activity can be regulated by NAD+, NADH and some NAD+ metabolites. In this study, SIRT3 expression was downregulated in the myocardial tissues of the ISO group, which could be related to an altered NAD/NADH ratio as a result of AngII stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt3, Sirt4, and Sirt5 were identified as mitochondrial deacetylases [ 79 ]. However, only Sirt3 is considered to be the major mitochondrial deacetylase [ 84 , 85 , 86 ].…”
Section: Effect Of Ischemia On Mitochondrial Metabolismmentioning
confidence: 99%
“…Apart from respiratory complexes and TCA cycle enzymes, enzymes of the mitochondrial antioxidative system, particularly MnSOD, are also hyperacetylated [ 56 ]. The increased acetylation of MnSOD inhibits the activity of this enzymes [ 88 ], and as a result, mitochondrial capacity to detoxify superoxide is compromised and mitochondria become a hot spot for ROS production ( Figure 3 ) [ 56 , 86 ].…”
Section: Effect Of Ischemia On Mitochondrial Metabolismmentioning
confidence: 99%